STRATEGI KOMUNIKASI KRISIS TUPPERWARE DALAM MENGHADAPI KEBANGKRUTAN - Annisa Bella Arsidyanthi; Saeful Mujab; Zerlinda Salsabila (Triwikrama: Jurnal Ilmu Sosial, 2025)
Tupperware is a global brand known for its household products, especially its innovative and efficient airtight plastic containers. Founded by Earl Tupper in 1946 in the United States, the company pioneered food storage and introduced a direct sales model through social events such as the Tupperware Party. However, in September 2024, Tupperware faced bankruptcy due to declining consumer demand, intense competition, and increasing debt. This crisis not only affected the company's operations but also reduced the trust of consumers and business partners.This study aims to analyze crisis communication strategies to restore Tupperware's image amid bankruptcy. The method used is a literature review to examine the steps of product innovation, digital transformation, and effective communication strategies with stakeholders. The results of this study are expected to be a guide in issue management and crisis communication, helping Tupperware face challenges in a more structured manner, rebuild consumer trust, and restore profitability. The right strategy is expected to not only save the company from the crisis but also provide lessons for future business management.